Kembara - Universitas Muhammadiyah Malang. Prodi Pendidikan Bahasa Indonesia (2015)
"Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya"
Keywords: Language and languages : Periodicals; Literature : Periodicals; Language and languages; Literature